A novel ionomeric polyurethane elastomer based on ionic liquid as crosslinker. Issue 101 (19th October 2016) - Behera, Prasanta Kumar; Usha, K. M.; Guchhait, P. K.; Jehnichen, Dieter; Das, Amit; Voit, Brigitte; Singha, Nikhil K.
Abstract : A novel flexible polyurethane was prepared using ionic liquid as crosslinker. It showed lower T g, superelastomeric behavior with very high elongation, better tensile and oil resistance properties than a non-ionic crosslinked PU or a linear PU. Abstract : A novel ionic liquid crosslinked flexible polyurethane elastomer (PUIL) was successfully synthesized by a one-pot polymerization method. A variety of characterization methods was employed to study the properties of PUIL, and they were compared with those of a linear thermoplastic polyurethane elastomer (TPU) prepared using butanediol (BDO) as a chain extender. A reference chemically crosslinked polyurethane (PUTMP) was also synthesized by using trimethylolpropane (TMP) as a non-ionic crosslinker. FT-IR spectroscopy revealed that the hydrogen bonding interaction was significantly suppressed in the presence of ionic liquid crosslinker leading to a highly flexible but tough elastomer material. Differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA) demonstrated the improved flexibility of PUIL, as the glass transition temperature ( T g ) of PUIL was lower than that of TPU and PUTMP. At the same time, PUIL exhibited a significantly higher tensile strength as well as higher elongation at break, as compared to TPU and PUTMP prepared without ionic liquid crosslinker. In the SAXS profiles, both TPU and PUIL showed single and broad peak characteristics of non-uniform microphase-separated morphology, whereas no phase separation was found in PUTMP. Contact angle measurement showed that the polarity of PUIL is higher than TPU and PUTMP, but importantly, the presence of ionic liquid crosslinks improved the oil resistance property.